« I was the only one of the family who wasn't quite sane » : être femme, épouse, mère et artiste dans The Creators (1910) de May Sinclair - Leslie de Bont (Cahiers Victoriens et Edouardiens)
This paper focuses on May Sinclair’s 1910 Künstlerroman The Creators, which revolves around the life and experience of Jane Holland, a successful writer, as well as of several other artist figures, both male and female. In the novel, female creation involves transgression as it is shown to be incompatible with most social, sexual and even statistical or medical norms. Yet, The Creators provides us with rather atypical reactions to the dialectics of feminine art and social norms: Jane Holland’s very modern conciliation between professional and family life and Nina Lempriere’s extreme androgynous attitudes, implying a new relation to norms, time and nature. We aim at analyzing the novel’s need to set up new discourses, instead of new norms, that try to encapsulate the feminine consciousness and experience of creation in Edwardian times.